Financial intermediation cost, rents, and productivity: An international comparison - Guillaume Bazot (European Historical Economics Society (EHES), 2018)
Calculation of the unit cost of financial intermediation for 20 countries from 1970 to 2015 has produced the following results. (i) Most countries' unit costs decline and converge in the long run. (ii) Unit costs were much higher in the 1970s and 1980s, coinciding with high nominal rates, as confirmed by panel cointegration tests. (iii) Countries' unit cost aggregation suggests a slight decrease in international unit cost whatever the set of hypotheses used in the calculation. (iv) The break down of unit costs into labor costs, capital costs, and profits shows that most of the decrease stems from reduced input costs. Gross operating surplus and total compensation per output tend to decline while distributed profit per output rises, suggesting increasing intermediation rents per output. (v) The productivity of labor in finance compared to other sectors tends to increase in most countries. (vi) The evidence suggests that most productivity gains have been captured by the financial sector in Canada, the UK, and the US. Elsewhere, productivity gains have benefited the nonfinancial sector through unit cost reduction. (vii) Deregulation is either negatively or not correlated with unit cost. In other words, deregulation is not related to unit cost increases. Finally, the paper discusses the consequences of those results for current debates about finance relative wage changes and inequalities.
Keywords: E3; E4; F3; G2; N2; 330; Unit cost; deregulation; convergence